Empirical evaluation of drivers’ operating speeds along curvatures on single carriageway roads - Che Puan, Othman (Penerbit UTM Press, 2015)
Choice of vehicle’s speed is one of the most important factors for a driver for proper vehicle’s control and selecting a wrong speed results in loss of vehicle’s control; particularly in negotiating road curvatures. Many of such speed related errors could be attributed to inconsistencies in the road alignment, that surprise the driver as a result of sudden change in road characteristics leading to an excess critical speed, hence, losing the vehicle’s control. This inconsistency should be accounted for and controlled by the engineers. This study was carried out to evaluate the speeds of the drivers when negotiating various layouts of road bends, determination of possible factors affecting drivers’ operating speed and development of prediction models for operational 85th percentile driver’s speed. Speeds of over 4000 vehicles (light and heavy) were collected at 10 road curves of various designs using speed radar meter and video recording system. Speeds were measured at three different points along the curves; the entry, mid and exit points. Preliminary findings from this study revealed that there are some inconsistencies in the features of the existing road curves. The design of the existing curves used in this study can be regarded as fair as the change in the operating speed of light vehicles was found to be higher than 10 km/h; being the established lower limiting value. Likewise, the road curves could also be regarded to fall within a fair and poor design because the average change in operating speed exceeded the limiting value of 20 km/h when compared with the posted speed limit. However, more data would be required to improve the accuracy of the results.